A Shared Memory Module for Asynchronous Arrays of Processors. (9th May 2007) - Meeuwsen, Michael J.; Yu, Zhiyi; Baas, Bevan M.
Abstract : A shared memory module connecting multiple independently clocked processors is presented. The memory module itself is independently clocked, supports hardware address generation, mutual exclusion, and multiple addressing modes. The architecture supports independent address generation and data generation/consumption by different processors which increases efficiency and simplifies programming for many embedded and DSP tasks. Simultaneous access by different processors is arbitrated using a least-recently-serviced priority scheme. Simulations show high throughputs over a variety of memory loads. A standard cell implementation shares an 8 K-word SRAM among four processors, and can support a 64 K-word SRAM with no additional changes. It cycles at 555 MHz and occupies 1.2mm 2 in 0.18μ m CMOS.